Reflection of Racial Discrimination in “Freedom Writers” Film’s Dialogs - Umi Hani; Aster Tania Nafiri Azzahra (Wanastra: Jurnal Bahasa dan Sastra, 2024)
This research aims to reflect on racial discrimination contained in the dialogue of Richard La Gravense's film Freedom Writers (2007). This film tells the story of a white teacher named Erin Gruwell who tries to resolve the racist conflict that occurred among her students at Woodrow Wilson High School in Long Beach, California. The film depicts how "liberating" education can be a beacon amid raging gang clashes that drag many children into a cycle of violence. Based on a true story, Freedom Writers, which debuted for the first time on the big screen in 2007, gives a strong impression of how fundamental the role of education is. This research approach is qualitative description. Data were analyzed based on Fred L. Pincus' theory of types of discrimination and Erving Goffman's theory of stigma. The results of this research conclude that in the dialogue of the film, the characters experience two types of acts of racial discrimination, namely individual discrimination and institutional discrimination. Apart from that, this treatment has an impact on prejudice, resulting in violence between racial groups.